Relationship between projected changes in future climatic suitability and demographic and functional traits of forest tree species in Spain (Climatic Change, 2013)
The response of plant species to future climate conditions is probably dependent on their ecological characteristics, including climatic niche, demographic rates and functional traits. Using forest inventory data from 27 dominant woody species in Spanish forests, we explore the relationships between species characteristics and projected changes in their average climatic suitability (occurrence of suitable climatic conditions for a species in a given territory) obtained by empirical niche-based models, under a business-as-usual climate change scenario (A1, HadCM3, 2001–2100). We hypothesize that most species will suffer a decline in climatic suitability, with a less severe for species (i) currently living in more arid climates or exhibiting a broader current climatic niche; (ii) with higher current growth rates; (iii) with functional traits related to resistance to water deficits. The analysis confirm our hypothesis since apart from a few Mediterranean species, most species decrease their climatic suitability in the region under future climate, characterized by increased aridity. Also, species living in warmer locations or under a wider range of climatic conditions tend to experience less decrease in climatic suitability. As hypothesized, a positive relationship was detected between current relative growth rates and increase in future climatic suitability. Nevertheless, current tree mortality did not correlate with changes in future climatic suitability. In contrast with our hypothesis, functional traits did not show a clear relationship with changes in climate suitability; instead species often presented idiosyncratic responses that, in some cases, could reflect past management. These results suggest that the extrapolation of species performance to future climatic scenarios based on current patterns of dominance is constrained by factors other than species autoecology, particularly human activity.
APSAPSThe following values have no corresponding Zotero field: publisher: Springer Netherlands

Drought-Induced Multifactor Decline of Scots Pine in the Pyrenees and Potential Vegetation Change by the Expansion of Co-occurring Oak Species - Galiano, L.; Martínez-Vilalta, J.; Lloret, F. (Ecosystems, 2010)
Episodes of drought-induced tree dieback have been recently observed in many forest areas of the world, particularly at the dry edge of species distributions. Under climate change, those effects could signal potential vegetation shifts occurring over large geographical areas, with major impacts on ecosystem form and function. In this article, we studied the effect of a single drought episode, which occurred in summer 2005, on a Scots pine population in central Pyrenees (NE Spain). Our main objective was to study the environmental correlates of forest decline and vegetation change at the plot level. General and generalized linear models were used to study the relationship between canopy defoliation, mortality and recruitment, and plot characteristics. A droughtdriven multifactor dieback was observed in the study forest. Defoliation and mortality were associated with the local level of drought stress estimated at each plot. In addition, stand structure, soil properties, and mistletoe infection were also associated with the observed pattern of defoliation, presumably acting as long-term predisposing factors. Recruitment of Scots pine was low in all plots. In contrast, we observed abundant recruitment of other tree species, mostlyQuercus ilexand Q. humilis, particularly in plots where Scots pine showed high defoliation and mortality. These results suggest that an altitudinal upwards migration of Quercusspecies, mediated by the dieback of the currently dominant species, may take place in the studied slopes. Many rear-edge populations of Scots pine sheltered in the mountain environments of the Iberian Peninsula could be at risk under future climate scenarios.
Keywords: canopy defoliation; Drought; mistletoe; mortality; pinus sylvestris l; Recruitment; scots pine; scots pine (Pinus sylvestris L.); soil properties; Stand Structure; summer; summer water availability; Water availability

Patterns of species impoverishment in managed forests of Catalonia (NE Spain) (Journal of Vegetation Science, 2009)
Question: In managed forests, woody plant richness shows great variations in pattern. Herein we try to elucidate the role of major factors, such as successional status, to explain this variation. Assuming that less competitive or disturbance-sensitive species will be systematically more prone to disappear, we investigate the existence of nonrandom patterns of species impoverishment – i.e., the number of species unable to attain maximal richness – and the ecological and successional status of species associated with impoverishment in relation to a regional climatic gradient. Methods: We explored species composition in approximately 7500 forest plots in Catalonia (NE Spain). We evaluated non-random patterns of species impoverishment by analyzing their nestedness. Multivariate analysis was used to relate environmental variables and impoverishment to species occurrence. Plot successional status and ecological range were also estimated from species composition, and species impoverishment was then correlated to these estimators. Results: Most forests show a non-random pattern of species loss: poor stands tend to retain the same species, and the species determining high richness tend to be the same. Late successional species tend to be more common in impoverished plots of drier and warmer forests, while species typical of open or disturbed habitats are more common in impoverished plots of moister and colder forests. Communities dominated by early or late successional species are mostly impoverished, while the richest stands are constituted by species of intermediate stages. Forests dominated by species with a narrow or wide ecological range showed high impoverishment levels, while the richest stands had species with an intermediate ecological range. Discussion: In warmer Mediterranean forests, impoverishment tends to be associated with late successional stages, while in moister and colder forests, species loss is more closely related to disturbance and exploitation. This study reveals the difﬁculties involved in using species richness as a simple descriptor of the degree of forest conservation. Identiﬁcation of dominant species and species indicative of ecological processes would constitute an easily applicable practice that would consolidate assessment of forests status.

Influence of fire severity on plant regeneration by means of remote sensing imagery - Díaz-Delgado, R.; Lloret, F.; Pons, X. (International Journal of Remote Sensing, 2003)
In this paper we analyse the interactions between fire severity (plant damage) and plant regeneration after fire by means of remote sensing imagery and a field fire severity map. A severity map was constructed over a large fire (2692 ha) occurring in July 1994 in the Barcelona province (north-east of Spain). Seven severity classes were assigned to the apparent plant damage as a function of burning intensity. Several Landsat TM and MSS images from dates immediately before and after the fire were employed to monitor plant regeneration processes as well as to evaluate the relationship with fire severity observed in situ . Plant regeneration was monitored using NDVI measurements (average class values standardized with neighbour unburned control plots). Pre-fire NDVI measurements were extracted for every plant cover category (7), field fire severity class (7), and spatial cross-tabulation of both layers (33) and compared to post-fire values. NDVI decline due to fire was positively correlated with field fire severity class. Results show different patterns of recovery for each dominant species, severity class and combination of both factors. For all cases a significant negative correlation was found between damage and regeneration ability. This work leads to a better understanding of the influence of severity, a major fire regime parameter on plant regeneration, and may aid to manage restoration on areas burned under different fire severity levels.
doi: 10.1080/01431160210144732doi: 10.1080/01431160210144732The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: dominant species (voyant); fire severity; NDVI; plant damage; plant regeneration